Kewenangan ASEAN Political-Security Community dalam Menghadapi Klaim Nine-Dash Line China - Nurhayati, Ema (PSHPM Untag Semarang, 2025)
This research analyzes the jurisdictional limitations of the ASEAN Political-Security Community (APSC) in addressing China's Nine-Dash Line claim in the South China Sea. Through a qualitative approach examining policy documents and recent academic literature, this study evaluates the effectiveness of instruments developed by APSC such as the Declaration on the Conduct of Parties (DOC) and the Code of Conduct (COC) negotiation process. The findings indicate that APSC's authority is constrained by several fundamental factors: the principles of non-intervention and consensus-based decision-making that create structural weaknesses, limitations in UNCLOS implementation due to China's rejection of the 2016 arbitration ruling, the dilemma of balancing